Exploring AI-Powered Speaking Applications on Learning Styles Accommodation Among Indonesian Senior High School Students - Cut Miftahul Salami; Muhammad Dalimunte; Farida Repelita Waty BR Kembaren (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This qualitative case study addresses the understudied interplay between students' diverse VARK learning styles (Visual, Auditory, Read/Write, Kinesthetic) and their engagement with an integrated AI-powered speaking platform, Practica AI, within the Indonesian socio-cultural context. The research was driven by the practical observation of varied learning outcomes among students using the same AI tool, suggesting a critical mediating role of individual learning styles. Conducted over three months at SMA Sukma Bangsa Lhokseumawe, the study employed a descriptive case study design with six purposefully selected 10th-grade participants representing a spectrum of VARK profiles. Data were collected through semi-structured interviews, non-participant observations, participant reflective journals, and document analysis (VARK questionnaires, app logs). Thematic analysis revealed three primary findings. First, learning styles functioned not as static labels but as dynamic strategic identities; students consciously curated personalized learning pathways by selectively navigating and combining Practica AI's multimodal features. Second, the study conceptualizes a critical "affordance-accessibility gap," where the effectiveness of a technological feature is contingent upon its alignment with the user's cognitive style, rendering the same feature a strength for one learner and a point of friction for another. Third, the research documents the significant cultural practice of "socializing the interface," where students collectively transformed the individualistic AI tool into a collaborative learning experience through peer comparison and shared scenario analysis, aligning with the local gotong royong (mutual assistance) ethos. Crucially, the study elucidates how these style-mediated experiences indirectly contribute to speaking skill improvement by fostering metacognitive awareness, reducing anxiety, and enabling targeted micro-skill practice. The study concludes that the efficacy of AI in language learning is co-constructed through the negotiation of intrinsic cognitive preferences, technological design, and the socio-cultural learning context. It underscores the urgent need for pedagogical strategies that foster metacognitive awareness and for instructional designs that are not only multimodal but also culturally responsive.